Strategic change and sensemaking practice: enabling the role of the middle manager. Issue 4 (2nd April 2020) - Kieran, Sarah; MacMahon, Juliet; MacCurtain, Sarah
Abstract : Purpose: The critical input of middle managers as they make sense of the organisation's plans is paramount during the process of strategic change. Through the lens of middle manager sensemaking literature, this explorative research identifies key organisational practices that underpin sensemaking. An understanding of these practices will allow organisations better develop and support them, thereby enabling middle managers' contribution to strategic change. Design/methodology/approach: This study employed an innovative diary methodology. 42 middle managers, across three organisations, completed a weekly, online diary for 12 weeks. A qualitative analysis of the final 355 diaries isolated and explained the sensemaking practices in which middle managers engaged as they sought to achieve the shared understanding required to progress strategic change. Findings: This study identifies the key practice underpinning middle manager sensemaking as formal and frequent discourse opportunities between leaders and middle managers. Through leader participation beyond the initiation stages of strategic change, and the organisation's positive positioning of time and metrics, these discourse opportunities enable a form of sensemaking associated with a number of positive organisational outcomes. These include middle manager sensegiving across the organisation, the successful enactment of strategic change, positive perceptions of change outcomes and organisational climate among middle managers and middle manager well-being. Research limitations/implications: This study advances our theoretical understanding of the practice of sensemaking in organisations through the isolation and identification of its key practices. However, given the difficulty in obtaining access for such a lengthy and intrusive methodology, the study is confined to three organisations. Additionally, the focus on the practice of sensemaking did not fully explore any contextual factors within these organisations. Also, middle manager perceptions of successful organisational outcomes are not very reliable performance indicators. While the self-reporting of perceptions is a worthwhile means of gathering data, a measure and comparison of actual business performance indicators would significantly strengthen the findings. Practical implications: From a practitioner perspective, this study not only underlines the importance for organisations of developing critical sensemaking practices for middle managers but also provides a clear pathway to achieving this. In approaching the intangible process of sensemaking from a practice perspective, it provides key stakeholders such as leaders, change agents and the HR department with a guide as to the types and forms of discourse practices which can be enabled. Maybe more importantly, it also highlights the practices which disable middle manager sensemaking. The study also provides organisations with insights into the positive outcomes stemming from middle manager sensemaking that should strengthen their case towards the development of sensemaking practices. Originality/value: This paper responds to the call for new approaches to the study of sensemaking as an ongoing practice within organisations. The qualitative diary analysis provides rich insights into the specific organisational practices that can enable middle manager sensemaking, while also highlighting those practices that can disable their role during strategic change. These findings provide organisations with clear approaches for developing sensemaking as a practice, thereby engaging and supporting the multiple actors and levels required to deliver successful strategic change.